Analysis Of Digital Leadership and Digital Transformation In Improving Public Services In The City Of Tasikmalaya - Amran Saefullah; Reza Faizal Anshori (Citakonsultindo, 2024)
Internet use has experienced a very significant increase. has become an integral part of everyday life, changing the way we learn, communicate, and even work. The Internet has revolutionized the way we communicate. Now, there are many conveniences with email, social media and instant messaging applications, so communication is faster and more efficient. The aim of this research is to analyze the role of digital leadership in realizing digital transformation in the government sector in order to improve the quality of public services. This research uses a qualitative approach, using the literature review method. This study was conducted to examine the role of digital leadership in the government sector in realizing digital transformation. Data was collected through previous literature originating from previous studies, journals and books related to the research problem. After exploring various literature, data, documents and discussions in the Focus Group Discussion, the implementation of digital leadership provides strength to leadership policies in regulating the use of information technology to solve problems collaboratively and with effective communication between leaders and members. This research concludes that the obstacles and obstacles encountered in services need to be immediately overcome by developing a digital transformation program to improve the quality of public services. Because the development of digital technology is very fast, it is necessary to anticipate the development of digital competency capacity for coordinators and members in a programmed, planned and measurable manner.